EXPERIENCE AND RESULTS OF DEVELOPING THE JAPANESE-KAZAKH DICTIONARY OF POLITICAL-ECONOMIC TERMS - Saito, А; Amantay, Zh B; Kadikova, S I (Journal of Oriental Studies, 2016)
This article considers the ways of developing of Japanese-Kazakh political-economic dictionary and the results of the questionary devoted to defining the quality of dictionary.